Attenuation of pharmaceuticals, nutrients and toxicity in a rural sewage lagoon system integrated with a subsurface filtration technology. (October 2018) - Chaves-Barquero, Luis G.; Luong, Kim Hoang; Rudy, Martina D.; Frank, Richard A.; Hanson, Mark L.; Wong, Charles S.
Abstract: Although many studies have addressed the ability of subsurface filtration systems to remove emerging contaminants from wastewater at micro- and mesocosm-scale, little is known about their performance on full-scale wastewater treatment facilities. To understand better how effective these systems can be for municipal wastewater polishing, we assessed the ability of a full-scale lagoon-subsurface filter system located in Dunnottar, Manitoba, Canada, to attenuate regulatory wastewater parameters, nutrients, pharmaceuticals, and toxicity over the course of the discharge periods in 2015 and 2016 (June–October). Pharmaceuticals included β-blockers, anticonvulsant drugs, and macrolide and sulfonamide antibiotics. Out of six consistently detected pharmaceuticals, four were efficiently removed through lagoon treatment (e.g. clarithromycin, metoprolol, propranolol), while two persisted to a certain extent (e.g. carbamazepine, sulfamethoxazole), even after subsurface filtration. Attenuation was observed for nutrients with averages of 40% and 60% for ammonia and total phosphorus respectively within the filter, consistent with previous pilot-scale studies at this facility. Compliance with regulations for conventional wastewater parameters at the effluent was observed, as well as reduced acute toxicity (as determined by Microtox ® ) from the primary lagoon to the effluent, and little likelihood of acute toxicity in receiving waters. Our results suggest that first, the full-scale system has an overall similar performance when compared to the previously studied pilot-scale system; second, there was no apparent effect of acclimation on the attenuation of studied contaminants or toxicity; and finally, the concentrations of contaminants do not appear to pose an acute risk for aquatic species in the receiving environment. Highlights: Performance of this full-scale system is similar to a previously studied pilot-scale system. No apparent effect of acclimation of the filter was observed for studied parameters. Most detected pharmaceuticals were removed from wastewater during lagoon treatment. Carbamazepine and sulfamethoxazole persisted after subsurface filtration. Detected contaminants do not pose an acute risk for aquatic species in receiving environment.